Some New Common Fixed Point Theorems under Strict Contractive Conditions in G-Metric Spaces - Zead Mustafa (Journal of Applied Mathematics)
We introduce some new types of pairs of mappings (𝑓,𝑔) on G-metric space called G-weakly commuting of type (𝐴𝑓) and G-R-weakly commuting of type (𝐴𝑓). We obtain also several common fixed point results for these mappings under certain contractive condition in G-metric space. Also some examples illustrated to support our results, and comparison between different types of pairs of mappings are studied.